2012
DOI: 10.1161/strokeaha.112.658500
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Stroke Mechanisms in Atherosclerotic Stroke

Abstract: Previous studies have addressed the differences in risk factors and stroke mechanisms between ICAS and ECAS, 2,3 but the results are inconsistent. Whereas some reported that hypertension, diabetes mellitus, and metabolic syndrome (MetS) are more closely associated with ICAS, 4-8 this was not confirmed by others. 9-11 It also remains unclear whether the risk factors and stroke mechanisms differ between anterior and posterior circulation atherosclerosis. 12Previous studies examined a small number of patients at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
148
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 266 publications
(161 citation statements)
references
References 25 publications
11
148
2
Order By: Relevance
“…23,24 Considering the high prevalence of HR-Dissection has been found to be another common finding in our cohort. Cervicocerebral artery dissection accounts for 1% to 2% of all ischemic strokes 25 and is one of the major causes of stroke in young patients.…”
Section: Discussionmentioning
confidence: 69%
“…23,24 Considering the high prevalence of HR-Dissection has been found to be another common finding in our cohort. Cervicocerebral artery dissection accounts for 1% to 2% of all ischemic strokes 25 and is one of the major causes of stroke in young patients.…”
Section: Discussionmentioning
confidence: 69%
“…Previous neuropathological studies demonstrated that a high incidence of subcortical infarctions in patients with DM, especially in the pons perfused by PPA (Baumgartner et al., 2003; Terai et al, 2000). A recent study showed that branch occlusion was a more important mechanism in posterior circulation diseases (Kim et al., 2012). Based on these reports, this study indicated that PPD is independently associated with HbA1c, compared with LD, which represented the control of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The PPA are 200–300μ min diameter and have less variation (Aronson, 1973). In the presence of parental atherosclerotic thrombosis, the smaller and shorter perforating vessels may be more susceptible to occlusion (Kim et al., 2012; Peress, Kane, & Aronson, 1973). Future researches are expected to explain the exact mechanism of the correlation with PPD and HbA1c.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly specific ethnic groups such as individuals of African, Hispanic, and Asian decent are genetically predisposed. 12 Lifestyle factors such as diet, exercise, and smoking play an important role, as do medical conditions such as hyperlipidemia, hypertension, and diabetes. Intraluminal narrowing of major intracranial vessels such as the internal carotid and basilar arteries-as well as secondary branches such as the anterior, middle, and posterior cerebral arteries-can place the patient in a state of cerebral hypoperfusion.…”
Section: Pathophysiology and Diagnosis Of Intracranial Atherosclerotimentioning
confidence: 99%